2019
DOI: 10.1039/c9ra01301f
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose transparent conductive film and its feasible use in perovskite solar cells

Abstract: A transparent conductive Ag nanowire (AgNW)-regenerated cellulose film (RCF) was prepared and has been proposed to be used as an anode for perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…Importantly, these cellulose and derivatives have some similar moieties with PEIE and MSAPBS, which can emerge as potential materials for the interface layer of OSC devices. Very recently, cellulose has been used as counter electrode for dye‐sensitized solar cells and flexible substrates for perovskite solar cells for green electronics by our group. Carboxymethyl cellulose sodium (CMC), one of the typical cellulose derivatives, can be prepared from rice straw and reed of agroforestry residues, and has been applied for different functions such as adhesive, stabilizer, and film former .…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, these cellulose and derivatives have some similar moieties with PEIE and MSAPBS, which can emerge as potential materials for the interface layer of OSC devices. Very recently, cellulose has been used as counter electrode for dye‐sensitized solar cells and flexible substrates for perovskite solar cells for green electronics by our group. Carboxymethyl cellulose sodium (CMC), one of the typical cellulose derivatives, can be prepared from rice straw and reed of agroforestry residues, and has been applied for different functions such as adhesive, stabilizer, and film former .…”
Section: Methodsmentioning
confidence: 99%
“…material for the photoactive components in solar cells because of its good charge transport properties, e.g., high surface areas and superior transparency. [88,112,114,150,151] For example, Zhu et al [112] reported a transparent and biodegradable conductive electrode derived from bamboo cellulose for flexible perovskite solar cells. The power conversion efficiency (PCE) of the bamboo cellulose-based solar cell is 11.68%, which is the highest efficiency among the reported biomass-based perovskite solar cells.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…24 Among these patterns, cellulose lms with excellent mechanical properties and other functionalities have been widely used in exible devices, photonics, uidic devices, packaging materials, electrochemical energy storage, and solar gain regulators. [25][26][27] In recent years, several approaches of preparing porous cellulose lms have recently received extensive attention, including electrospinning (modied cellulose acetate lms), 28 a paper-making like process (mesoporous Cladophora cellulose lms), 29 forcespinning (forcespinning cellulose acetate lms, FS-CA) 30 and phase inversion. 31 Moreover, many studies have focused on the use of cellulose derivatives and bacterial cellulose as matrix, or mixing cellulose with other ingredients to prepare the porous lm, and further improvement in porosity is required.…”
Section: Introductionmentioning
confidence: 99%